(untitled) (Economic Journal of Nepal, 2021)
Persistent deficit in trade balance is a common characteristic of developing countries in which low value agricultural exports may not offset the high value industrial imports. This article intends to explore the effect of inflation, exchange rate, GDP, FDI and GCE on trade balance of South Asian countries: Bangladesh, Bhutan, India, Nepal, Pakistan and Sri Lanka. Data were obtained from, World Development Indicators from 2001 to 2019 published by World Bank. Initaly, the trend of all variables was monitored using graphs. Then, fixed effect model was applied as suggested by Hausman test in which only exchage rate was found significantly negatively related with trade balance. Due to serial correlation problem with fixed effect mode, data were further analysed through panel ARDL / PMG and found the evidences of long-run relationship among the variables. It was also found that inflation, exchange rate, and GDP had significant positive relationship with trade balance in long-run whereas GCE had significant negative impact on it. Interestingly, FDI did not have significant contribution on trade balance in long-run. None of variables were found to be significant in short run. However, all selected variables affected signifcantly to trade balance in short-run while testing cross-section wise. Finding of this research has an important implication to South Asian countries for making concensus in desiging common currency to fight against the growing concern of trade deficit in the region.